The Practice of Sharing Production from Cattle from a Sharia Economic Law Perspective - Muh. Ilham; Ridha Jafar, Ahmad (ETDC: Indonesian Journal of Research and Educational Review, 2023)
The problems studied in this research are regarding the practice of sharing cattle and livestock results in the community in Limpomajang sub-district, Majauleng sub-district, and Wajo Regency. The purpose of this research is to find out how profit-sharing contracts (mudharabah) are practiced in the community and to find out the perspective of Sharia economic law regarding the system used. In this research, the method used is field research with a normative approach; and the data analysis used is the Miles and Huberman model of data analysis. The informants in this research are people who keep cattle and who own cattle in Limpomajang Village. The results of the research show that in the practice of sharing cattle products from a Sharia economic law perspective in the community, there are no elements of gharar and dharar contained in this collaboration because the cooperation implemented is based on the principles of trust and kinship. The cattle owner (shahibul mal) bears the costs of medicine and rope, and the cattle breeder (mudharib) is responsible for looking after the cattle entrusted to him. The principles applied are based on the principles of trust and kinship as well as the pleasure of both parties. Apart from that, mutual trust and a spirit of mutual assistance are also the main foundations for the community to implement this kind of cooperation agreement.